Pressure Sores Prevention for Paraplegic People: Effects of Visual, Auditory and Tactile Supplementations on Overpressures Distribution in Seated Posture - Olivier Chenu; Yohan Payan; P. Hlavackova; Jacques Demongeot; Francis Cannard; Bruno Diot; Nicolas Vuillerme (Applied Bionics and Biomechanics)
This paper presents a study on the usage of different informative modalities as biofeedbacks of a perceptual supplementation device aiming at reducing overpressure at the buttock area. Visual, audio and lingual electrotactile modalities are analysed and compared with a non-biofeedback session. In conclusion, sensory modalities have a positive and equal effect, but they are not equally judged in terms of comfort and disturbance with some other activities.